2010
DOI: 10.1037/a0020040
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory examination of the associations among racial and ethnic discrimination, racial climate, and trauma-related symptoms in a college student population.

Abstract: In this study, we examined the association among perceptions of racial and/or ethnic discrimination, racial climate, and trauma-related symptoms among 289 racially diverse college undergraduates. Study measures included the Perceived Stress Scale, the Perceived Ethnic Discrimination Questionnaire, the Posttraumatic Stress Disorder Checklist-Civilian Version, and the Racial Climate Scale. Results of a multivariate analysis of variance (MANOVA) indicated that Asian and Black students reported more frequent exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
156
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(174 citation statements)
references
References 59 publications
15
156
3
Order By: Relevance
“…The period of emerging adulthood-between the ages of 18 and 25-is characterized by identity exploration, which may be a challenging developmental stage for college students who are bicultural (Phinney, 2006). Compared to their monocultural peers, bicultural college students face more difficulties resulting from the transition to a new cultural environment such as a mismatch between personal and university values, racial discrimination, and challenges maintaining ties to heritage communities (Carter, Locks, & WinkleWagner, 2013;Pieterse, Carter, Evans, & Walter, 2010;Stephens, Fryberg, Markus, Johnson, & Covarrubias, 2012). These struggles can manifest as increased internalizing symptoms and antisocial behavior (Arbona & Jimenez, 2014;Miller, Yang, Farrell, & Lin, 2011;Park, Schwartz, Lee, Kim, & Rodriguez, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The period of emerging adulthood-between the ages of 18 and 25-is characterized by identity exploration, which may be a challenging developmental stage for college students who are bicultural (Phinney, 2006). Compared to their monocultural peers, bicultural college students face more difficulties resulting from the transition to a new cultural environment such as a mismatch between personal and university values, racial discrimination, and challenges maintaining ties to heritage communities (Carter, Locks, & WinkleWagner, 2013;Pieterse, Carter, Evans, & Walter, 2010;Stephens, Fryberg, Markus, Johnson, & Covarrubias, 2012). These struggles can manifest as increased internalizing symptoms and antisocial behavior (Arbona & Jimenez, 2014;Miller, Yang, Farrell, & Lin, 2011;Park, Schwartz, Lee, Kim, & Rodriguez, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These comments and actions are designed to undermine the legitimacy of their targeted victims, and, when combined with racialized microaggressions, their primary aim is to denigrate Faculty Women of Color -to reject and to quash them completely. Numerous studies have repeatedly shown that such scornful, offensive remarks and actions can exert a negative impact on individuals' emotional and physical health, affecting performance and productivity (Flores, Tschann, Dimas, Pasch, & de Groat, 2010;Lambert, Herman, Bynum, & Ialongo, 2009;Pieterse, Carter, Evans, & Walter, 2010;Wei, Alvarez, Ku, Russell, & Bonett, 2010). When Faculty Women of Color are confronted with such microaggressions daily, they envision themselves within an oppressive environment, one that neither respects nor protects them.…”
mentioning
confidence: 99%
“…Sport plays a role in supporting racial and ethnic identity development in higher education, which in turn helps promote cultural understanding (Beamon, 2014;Karkouti, 2015;Pieterse, Carter, Evans, & Walter, 2010). The development of racial and ethnic identity in higher education is important, but research on the nexus of international students, sports, and the development of racial and ethnic identity is limited.…”
Section: Significance Of the Researchmentioning
confidence: 99%
“…While stereotyping of varsity athletes often carries negative connotations over to off-the-field activities (Beamon, 2014;Feltz, Schneider, Hwang, & Skogsberg, 2013;Simons, Bosworth, Fujita, & Jensen, 2007), participation in student affairs activities like recreational sports in higher education can help at-home students understand their racial and ethnic identity (Karkouti, 2015;Pieterse et al, 2010).…”
Section: Sport and The Othermentioning
confidence: 99%